Urban 5G regulation: local licensing versus coopetition - A. Basaure; B. Finley (International Telecommunications Society (ITS), 2019)
Deployment of 5G networks is often described as a disruptive phenomena. Specifically 5G should enable new emerging Internet of Things (IoT) applications. However, such applications require new regulation and business models to incentivize costly infrastructure investments. Currently, no clear consensus exists on the appropriate regulatory regime for 5G urban deployment. This work explores two alternative regulatory scenarios for a connected vehicles scenario to analyze how the most important regulatory decisions affect an urban network deployment. One alternative is to maintain the current scheme of spectrum assignment while facilitating additional flexibility for infrastructure sharing (ex-post competition). The other alternative is to define local areas for monopoly 5G provisioning and define the conditions for competition ex-ante. Through agent-based simulations, this work shows that a local licensing scenario may achieve a better performance than a coopetition scenario. Additional sensitivity checks also help detail the existing trade-offs. Finally, the work discusses the implications and limitation of the findings.
Keywords: 330; 5G; IoT; connected cars; regulation; local licensing; coopetition; ex-ante versus ex-post competition